Korean Messiahs: Victory Altar and the Koreanization of Protestantism - Rigal-Cellard, Bernadette (Religions, 2024)
This paper analyses the indigenization or Koreanization of Protestantism in South Korea in the late 20th century through a study of an original messianic and millenarian movement, Victory Altar. The group was founded in 1981 by Cho Hee-Seung in the biblical tradition, with references to Korean spiritual traditions as well. Its most salient feature is the self-consecration of Cho Hee-Seung as “Victor Christ and God”, the unique universal Messiah. In order to show the correlation between this spiritual movement, Protestantism, and Korean culture, I survey the recent history of South Korea and its staunch nationalism largely spurred by Protestant missionaries at the turn of the 20th century. I then present the core teachings of Cho the Messiah: the biological immortality of neohumans, the Hebrew genealogy of the Koreans thanks to the saga of the Lost Tribe of Dan from Israel to Korea, and his major vows to protect South Korea. An assessment of the heritage of Protestantism in this movement is then offered through the perspective of post-colonialism since Victory Altar sees itself and its Messiah/God as far superior to the God and Messiah of the Western powers that brought Christianity to Korea without really understanding it.